The relationship of cerb B 2 expression with estrogen receptor and progesterone receptor and prognostic parameters in endometrial carcinomas - Kandemir Nilufer; Barisik Nagehan; Keser Sevinc; Gul Aylin; Cakır Caglar; Sensu Sibel; Karadayi Nimet (BMC, 2010)
Abstract Background Endometrial carcinoma (EC) is the most common malignancy of the female genital tract. Gene alterations and overexpression of various oncogenes are important in tumor development. The human HER 2 neu (c-erbB-2) gene product is a transmembrane receptor with an intracellular tyrosine kinase that plays an important role in coordinating the endometrial growth factor receptor signaling network. The aim of this study was to investigate the expression of c-erbB-2 in endometrial cancer, to study its correlation to established prognostic parameters and estrogen receptor (ER) and progesterone receptor (PR) status. Methods Immunohistochemical (IHC) analyses of ER, PR and c-erbB-2 were performed in 72 EC cases. Results We detected a positive staining with c erbB 2 in 18.1% of the cases and determined a statistically significant relation between c-erbB-2 and PR. We could not find a statistically significant relation between c-erbB-2 staining and ER. There was not a statistically significant difference between c-erbB-2 and histological grade. The highest level of c-erbB-2 was found in grade 2 cases. There was not any statistically significant relation between c-erbB-2 and menstrual status, myometrial invasion, lymph node status, stage and survival. Conclusions Although our study provides additional evidence of the potential prognostic role of c-erbB-2, further prospective and controlled studies are required to validate their clinical usefulness.